Estrogen and cancers of the colorectum, breast, and lung in postmenopausal women. (1st July 2015) - Honma, Naoko; Hosoi, Takayuki; Arai, Tomio; Takubo, Kaiyo
<x xml:space="preserve">Abstract</x> As estrogens play an important role in maintaining physiological function in various organs, the estrogen decrease after menopause is thought to cause various diseases frequently observed in postmenopausal or elderly women. With the aging of society and a decrease in infectious or vascular diseases, neoplasms have now become the most frequent cause of death in Japan. Cancers of the colorectum, breast, and lung have been rapidly increasing both in incidence and death, especially among postmenopausal women. Interestingly, all three of these cancers are associated with estrogens. In premenopausal women, ovarian estrogens plays major roles in the female reproductive organs through the classic estrogen receptor, ER‐α. In postmenopausal women, however, estrogens produced/activated by peripherally localized estrogen‐metabolizing enzymes such as aromatase, which converts androgen into estrogens, are thought to play physiologically and pathobiologically important roles in various organs through second ER, namely ER‐β, distributing systemically. In this article, the association of estrogens with these cancers in postmenopausal or elderly women are reviewed, especially focusing on the role of ER‐β and peripheral estrogen metabolism. The possibility of prevention or treatment of these diseases through estrogenic control is also discussed.